Association of the 103I MC4R allele with decreased body mass in 7937 participants of two population based surveys. Issue 4 (1st April 2005) - Heid, I M; Vollmert, C; Hinney, A; Döring, A; Geller, F; Löwel, H; Wichmann, H-E; Illig, T; Hebebrand, J; Kronenberg, F
Abstract : Background: The melanocortin-4-receptor gene ( MC4R ) is part of the melanocortinergic pathway that controls energy homeostasis. In a recent meta-analysis, the MC4R V103I (rs2229616) polymorphism was shown to be associated with body weight regulation. Although no functional differences between the isoleucine comprising receptor and the wild type receptor have been detected as yet, this meta-analysis of 14 case–control studies reported a mild negative association with obesity (odds ratio (OR) 0.69, p = 0.03). However, evidence in a large population based study in a homogeneous population and a significant estimate of the change in quantitative measures of obesity is still lacking. Methods: We analysed the data of two surveys of a white population with the same high quality study protocol, giving a total of 7937 participants. Results: By linear regression, we found a significant decrease of 0.52 body mass index (BMI) units (95% confidence interval (CI) −0.02 to −1.03, p = 0.043) for carriers of the heterozygote rs2229616G/A genotype, which was observed in 3.7% of the participants. Logistic regression yielded a significantly negative association of the MC4R variant with "above average weight" (BMI ⩾ median BMI) yielding an OR of 0.75 (95% CI 0.59 to 0.95 p = 0.017). We obtained similar results comparing obese (BMI ⩾30 kg/m 2, World Health Organization results for 1997) with non-obese (BMI <30 kg/m 2 ) participants. The results were found for both sexes and each survey separately, and did not depend on the modelling of age, sex, or survey effects. Conclusions: Our study confirms previous findings of a meta-analysis that the relatively infrequent G/A genotype of the V103I MC4R polymorphism is negatively associated with above average weight and obesity in population based original data of 7937 participants, and extends previous findings by showing for the first time a significantly lower BMI in individuals carrying the infrequent allele of this MC4R variant.